Quality assessment of synthetic speech - Stefan Brachmański; Maurycy Kin; Piotr Kozłowski (International Journal of Electronics and Telecommunications)
This paper presents the results of a subjective study of the quality assessment of several selected speech synthesizers. The subjects of the study were logatom intelligibility and overall speech signal quality evaluation. Synthesizers generating both male and female voices were used for the study. An attempt was also made to apply objective quality assessment methods used to test the quality of transmission in telecommunications channels. The results of these attempts, however, showed the impossibility of using the PESQ method to assess the quality of synthetic speech, mainly due to the lack of temporal synchronization between the test signal and the reference signal.